IMPLEMENTATION OF PROJECT-BASED MATHEMATICS LEARNING IN THE INDUSTRIAL WORK PRACTICE PROGRAM (PRAKERIN) FOR PANCARAN BERKAT VOCATIONAL SCHOOL STUDENTS - Purba, Jesica Triani (Journal of Learning on History and Social Sciences, 2025)
Objective: This study aims to analyze the implementation of project-based mathematics learning in Industrial Work Practice (Prakerin) programs at SMK Pancaran Berkat. Method: This qualitative descriptive study employed observations, interviews, and documentation of students and teachers during the internship. Results: The integration of mathematics in Prakerin through project-based learning improved students' problem-solving abilities, collaboration, and motivation. They also better understood the relevance of mathematical concepts in industrial contexts such as measurement, statistics, and cost calculation. Novelty: This study highlights how contextual project-based mathematics learning can serve as an interdisciplinary bridge between school-based theory and real-world industrial practice.